A Beginner’s Guide to Puzzle Design: Creating an applied guide for effective puzzle design in videogames - Prinz, Erik (University of the Witwatersrand, Johannesburg, 2023)
While a vast collection of information exploring effective puzzle design exists, it is riddled with conflicting opinions and inconsistent formats, making it arduous to engage with. This research aims to curate this collection, organizing its knowledge into an applied guide for puzzle design in videogames. This will be accomplished through an amalgamation of design principles offered by selected works of oundational literature, and the insights contained within the design philosophies of three industry professionals (Jonathan Blow, Kim Swift, and Arvi ‘Hempuli’ Teikari). The synthesis of these two families of information will be aided by the simultaneous development of a puzzle platforming videogame. Through a process of iteration and playtesting, this game will be used to assess the value and accuracy of the developing guide. With careful consideration of useful structures present in the foundational literature, the plethora of existing information can be reformatted to be user-friendly and appliable by novel puzzle designers.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Arts, in Digital Arts, to the Faculty of Humanities, Wits School of Arts, University of the Witwatersrand, Johannesburg, 2023.
Keywords: Puzzle; Puzzle Design; Puzzle Game; Game Design; Videogames; Video Games; Platformer; Guide; Guide Design; Playtest; Playtesting; UCTD; SDG-9: Industry, innovation and infrastructure